Effect of Processing Conditions on the Physical, Chemical and Transport Properties of Polylactic Acid Films Containing Thymol Incorporated by Supercritical Impregnation - Guarda-Moraga, A; Rodriguez-Mercado, F; Romero-Figueroa, J; Galotto-Lopez, M; Rojas-Sepulveda, A; Torres-Mediano, A; Villegas-Vallejos, C (Elsevier Ltd, 2017)
This study deals on the supercritical impregnation of thymol in polylactic acid (PLA) in order to obtain biodegradable antimicrobial films by means of a procedure, which is in agreement with the principles of green chemistry, reducing the environmental impact of products and of its preparation processes. The impregnation tests were carried out in a high-pressure cell using supercritical carbon dioxide as impregnation medium at different operational conditions. These assays were implemented at pressures of 9 and 12 MPa, a constant temperature equal to 40 °C and different values of depressurization rates: 0.1, 1.0 and 10 MPa min−1. Depending on the impregnation process conditions, thymol was incorporated into the films at concentrations from 13.5 to 20.5 %w/w. FTIR analyses confirmed the presence of thymol on the surface of the films. Furthermore, the supercritical impregnation process at the conditions used in this work produced a strong modification of the thermal and mechanical properties of the PLA films. On the other hand, release kinetic assays were carried out on the all prepared films. From these experimental results, it can be observed that the highest amounts of released thymol at the slowest depressurization rate were obtained. Meanwhile, the use of a previously reported mass transfer model shows that there is no significant effect of the supercritical impregnation process on the transport properties of PLA. From the experimental and theoretical results obtained in this work, it could be suggested that the impregnation of thymol in PLA using dense carbon dioxide is a promising technique to prepare active biodegradable materials for a wide range of applications. © 2017 Elsevier Ltd